2006
DOI: 10.1097/00000542-200605000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Common Inhalation Anesthetic Isoflurane Induces Apoptosis and Increases Amyloid β Protein Levels

Abstract: A clinically relevant concentration of isoflurane induces apoptosis, alters APP processing, and increases Abeta production in a human neuroglioma cell line. Because altered processing of APP leading to accumulation of Abeta is a key event in the pathogenesis of Alzheimer disease, these findings may have implications for use of this anesthetic agent in individuals with excessive levels of cerebral Abeta and elderly patients at increased risk for postoperative cognitive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
248
1
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(263 citation statements)
references
References 27 publications
8
248
1
6
Order By: Relevance
“…The latter has become more pertinent in the advent of an aging population and increasing awareness of the interplay between the perioperative inflammatory state, anesthetic agents, and neurodegenerative processes. [47][48][49][50][51] Assessment of cognitive recovery has thus progressed from simple assessments of orientation and comprehension 38,41,46 to more formal neuropsychological-based assessment. 26,37,52,53 More recent clinical recovery assessment tools, such as the Postoperative Quality of Recovery Scale (PostopQRS), 37 assess cognitive recovery by applying formal neuropsychological tests in truncated form and assessing patient recovery in relation to individual baseline function both in real time and over multiple time points.…”
Section: Measurement Of Recoverymentioning
confidence: 99%
“…The latter has become more pertinent in the advent of an aging population and increasing awareness of the interplay between the perioperative inflammatory state, anesthetic agents, and neurodegenerative processes. [47][48][49][50][51] Assessment of cognitive recovery has thus progressed from simple assessments of orientation and comprehension 38,41,46 to more formal neuropsychological-based assessment. 26,37,52,53 More recent clinical recovery assessment tools, such as the Postoperative Quality of Recovery Scale (PostopQRS), 37 assess cognitive recovery by applying formal neuropsychological tests in truncated form and assessing patient recovery in relation to individual baseline function both in real time and over multiple time points.…”
Section: Measurement Of Recoverymentioning
confidence: 99%
“…Perioperative factors, including hypoxia (Kokmen et al, 1996; Jendroska et al, 1997; Nagy et al, 1997; Snowdon et al, 1997; Kalaria, 2000), hypocapnia (Xie et al, 2004), and anesthetics (Eckenhoff et al, 2004;Xie et al, 2006a), have been reported to potentially contribute to AD neuropathogenesis. These perioperative factors may also cause postoperative cognitive dysfunction, a dementia associated with surgery and anesthesia, by trigging AD neuropathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with a commonly used inhalation anesthetic isoflurane (1.2-2.5% for 6 h) has been shown to enhance A␤ aggregation and cytotoxicity in pheochromocytoma cells (Eckenhoff et al, 2004). We recently showed that a clinically relevant concentration (2%) of isoflurane can induce apoptosis, alter APP processing, and increase production of A␤ in H4 human neuroglioma cells (Xie et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Of course it should be noted that symptomatic pre-operative neurological diseases, including dementia and any disorders of the central nervous system, are considered as exclusion criteria for studies concerning POCD (Monk et al, 2008). Data from experimental models pose the suggestion that exposure to inhaled anaesthetics increases cerebral pathological findings that are normally observed in Alzheimer's disease, including the increase of β-amyloid (Xie et al, 2006). Furthermore, hypothermia during anaesthesia induces hyperphosphorylation of proteins by reducing the phosphatase 2a activity (Planel et al, 2008).…”
Section: Neurological Diseasesmentioning
confidence: 99%
“…Furthermore, hypothermia during anaesthesia induces hyperphosphorylation of proteins by reducing the phosphatase 2a activity (Planel et al, 2008). Finally, it is noteworthy that anaesthesia, only at higher concentrations and prolonged periods, has been reported to produce pathological lesions similar to those of Alzheimer's disease but this is also a fact which is being disputed (Xie et al, 2006;Xie et al, 2007;Donk et al, 2012).…”
Section: Neurological Diseasesmentioning
confidence: 99%